Income distribution and economic cycles in an open economy supermultiplier model - Ariel Dvoskin; Matias Torchinsky Landau (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2022)
Supermultiplier growth models show that higher autonomous spending leads to stronger economic growth, implying that greater government spending can boost economic activity (Freitas and Serrano, 2015). However, several authors highlighted the limits of this strategy, arguing that increased spending might lead to unsustainable debt accumulation patterns. This is particularly important for small open economies, where growth requires imports that must be paid with foreign currency, which can lead to growing external indebtedness (Thirlwall, 1979; Nikiforos, 2018; Oreiro and Costa Santos, 2019). We build a structuralist supermultiplier model for a small open economy with two sources of autonomous demand, government expenditures and exports. We account for the dynamics of external indebtedness (determined by economic activity), wage growth (related to wage resistance) and the exchange rate (determined by the Central Bank but limited by international reserves constraints). We find that, in the long run, there is a limit for government spending: its growth rate cannot exceed that of exports without generating an external crisis. However, there is a strong role for public policy: there is nothing that automatically leads the economy to its maximum growth rate compatible with the external constraint to growth, and if government expenditures grow less than exports, the economy will not completely exploit its external space. But the main contribution of the paper is in the short-run analysis, where we find an additional restriction, related to income distribution. Since higher wages increase consumption and economic activity, they also require more imports, potentially leading to unsustainable debt growth. Therefore, there is a maximum real wage compatible with external equilibrium (Canitrot, 1983). If unions' demand wages are lower than the external equilibrium wage, the economy will be stable, but will also achieve unnecessarily low output and real wages. On the contrary, if target wages exceed those compatible with external equilibrium, the economy displays economic cycles between capacity utilisation, income distribution and indebtedness, marked by permanent inflation. We show that, in the short run, the government can optimize fiscal and monetary policies to maximise output given the external space, but that in the long run, economic growth requires not only domestic spending but also increasing exports to be sustainable.
Keywords: 330; Sraffian supermultiplier; Thirlwall's law; fiscal policy; income distribution; structuralism